Quantification of Siderophore and Hemolysin from Stachybotrys chartarum Strains, Including a Strain Isolated from the Lung of a Child with Pulmonary Hemorrhage and Hemosiderosis - Vesper, Stephen J. (American Society for Microbiology, 2000)
A strain of Stachybotrys chartarum was recently isolated from the lung of a pulmonary hemorrhage and hemosiderosis (PH) patient in Texas (designated the Houston strain). This is the first time that S. chartarum has been isolated from the lung of a PH patient. In this study, the Houston strain and 10 strains of S. chartarum isolated from case (n = 5) or control (n = 5) homes in Cleveland were analyzed for hemolytic activity, siderophore production, and relatedness as measured by random amplified polymorphic DNA analysis.